1974
DOI: 10.1136/bjo.58.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory tests for chlamydial infection. Their role in epidemiological studies of trachoma and its control.

Abstract: The isolation and serial cultivation of chlamydial organisms from trachoma (Tang, Chang, Huang, and Wang, 1957; Collier and Sowa, I958) and from inclusion blennorrhoea or paratrachoma (Jones, Collier, and Smith, I959), together with the proof that these TRIC agents cause these diseases (Collier, Duke-Elder, and Jones, I958, i96o; Jones and Collier, I962) have opened the way to the development of a variety of laboratory tests that can indicate infection by Chlamydia, including those that cause trachoma and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…It confirms the diagnosis in doubtful cases, gives a measure of the reservoir of infection in the community and is helpful in monitoring the effect of control programmes (Dawson, Jones & Tarizzo, 1981;Jones, 1974).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It confirms the diagnosis in doubtful cases, gives a measure of the reservoir of infection in the community and is helpful in monitoring the effect of control programmes (Dawson, Jones & Tarizzo, 1981;Jones, 1974).…”
Section: Introductionmentioning
confidence: 94%
“…All these techniques are well suited to work under field conditions, but scraping the conjunctiva with a sharp metal blade is painful, frequently causes bleeding in patients with active trachoma, and is likely to lead to resentment and lack of co-operation among populations investigated. Isolation 84 D. C. W. MABEY AND S. BOOTH-MASON in irradiated or cycloheximide-treated McCoy cells is more sensitive than any of these techniques (Jones, 1974;Schachter et al 1978) and does not require conjunctival scrapings since cotton-wool swabs have been shown to yield as many positives as scrapings by this technique . It is therefore the method of choice at present.…”
Section: Introductionmentioning
confidence: 99%
“…Because these epitopes are common to all chlamydial species (59), the specificity of the test was low (230). Additionally, it had low sensitivity for ocular infections (108,214).…”
Section: Serologymentioning
confidence: 99%
“…The authors suggested that the differing serovars of some of the adults was probably a reflection of infection in their youth. The three exceptions of children in the 31 families were two with evidence of both B and C infections and one with serovar D. This latter finding along with reports of infections in Gambia with serovar D [16], in Iran with serovar D [13], in South Africa with serovars D/E, F and K [1], and serovar J in a Navajo Indian child with trachoma in the United States [12] may indicate that, given the appropriate epidemiologic milieu, serovars of C. trachomatis other than A, B, Ba, and C can cause endemic trachoma. In microbiologically monitored transmission trials in a village in southern Iran, only C. trachomatis isolates of the A and B serovars were found in the original survey [25,26].…”
Section: Trachomatis Transmission Studiesmentioning
confidence: 50%